HUBUNGAN PENDIDIKAN IBU DAN DUKUNGAN ORANG TUA DENGAN TINGKAT KECEMASAN REMAJA SAAT MENARCHE DI MTS. A CIREBON - Rahayu, Rosalia (Jurnal Kesehatan Mahardika, 2023)
Adolescence is known as puberty, marked by the arrival of the first menstruation (menarche) in young women. Some students who experience menarche feel anxious, confused, sad, tremble, become uncaring, or feel proud of themselves for becoming adults. Menarche causes anxiety in young women due to a lack of information and understanding about it. The purpose of this study was to determine the relationship between mother's education and mother’s support, and anxiety levels in adolescents during menarche. This descriptive correlational research used a retrospective approach. The population in this study consisted of 154 female students who had experienced menarche, and the sample included 61 students. The results show that mother’s support are related to anxiety levels during menarche. In conclusion, a teenager's readiness to face menarche is influenced by the mother's education, and parental support during menarche helps teenagers understand physiological changes, enabling them to anticipate and overcome anxiety about menarche.